(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Vataja Kasa (presented by Shushka Kasa, Prasakta Vega, Shirah Shoola, Hrit Shoola, Parshwa Shoola, Swara Bheda and kshamana) has an increasing prevalence overtime due to the external influences such as industrialisation, urbanisation, environmental pollution and population explosion. Since it’s a demanding health concern, Vataja Kasa was taken up for the present clinical study and was approximately co-related to Tropical Pulmonary Eosinophilia (TPE) which is an immune hyper-responsiveness to microfilariae trapped in the lungs, characterised by paroxysmal nocturnal cough, breathlessness, wheezing, chest pain, scanty sputum production and eosinophilia. The study was conducted with the prime aim of assessing the efficacy of the trial drugs Vishwadi Leha and Bharangyadi Leha in the management of Vataja kasa – TPE. The Clinical trial included 40 patients of Vataja Kasa categorized into two groups (20 in each). In Group A-Vishwadi Leha (3 gms) and in Group B- Bharangyadi Leha (3 gms) were administered thrice daily along with quantity sufficient warm water after food for 30 days. The findings were recorded, assessed and graded accordingly on the 14th and 30th day. The results were analysed statistically for ‘p’ value using student’s paired t-test before and after treatment. Significant results (p<0.001) were observed in both groups. Comparative study between percentages of improvement in Group A showed 5% (based on subjective parameters) and 7% (based on objective parameters) more improvement than that of Group B. Based on the results, it was concluded that Vishwadi Leha has a slightly better result than Bharangyadi Leha in the management of Vataja Kasa-TPE.